Graphene Oxide Thin Films: Synthesis and Optical Characterization - Prías Barragán, J. J.; Gross, K.; Darío Perea, José; Killilea, Niall Andrew; Heiß, Wolfgang; Brabec, Christoph; Calderón, H. Ariza; Prieto, Pedro (ChemistrySelect, 2020)
The oxidized derivative of graphene named Graphene oxide (GO) are attractive materials as optoelectronic devices due to their optical response in the mid-infrared wavelength spectral range; however, very large-scaled synthesis methods and optical characterization are required. Here, GO thin films are fabricated on quartz by implementing simple two-step pyrolysis processes by using renewable bamboo as source material. The effect of carbonization temperature (TCA) on the compositional, vibrational, and optoelectronic properties of the system are investigated. It was found that as TCA increases, graphite conversion rises, oxygen coverage reduces from 17 % to 4 %, and the band-gap energy monotonically decreases from 0.30 to 0.11 eV. Theoretical predictions of the energy band-gap variations with the oxide coverage obtained via density functional theory (DFT) computational simulations agree well with the experimental results, providing evidence of oxygen-mediated charge-transport scattering. Interestingly, in the optical response, increased TCA results in a blue-shift of the absorption and the absorbance spectrum can be correlated with the large size distribution of the graphitic nano-crystals of the samples. These results suggest that graphene oxide-bamboo pyroligneous acid (GO) thin films exhibit optoelectronic response useful in developing photodetectors and emitter devices in the mid-infrared (MIR) spectral range.
CRIS-Team Scopus Importer:2020-10-23
Keywords: band-gap energy; COSMO-RS; DFT computational simulations; graphene oxide; HR-TEM images; oxygen coverage; Photoluminescence; UV-Vis